HUMAN RESOURCE MANAGEMENT CONCEPT - Anggraini, Eva; Alqoisya, Naswan; Nuraeny, Iin; Fauziah, Lulu Fauziah; Huda, Miftahul; Hadiati, Eti (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Human Resource Management (HRM) plays a pivotal role in ensuring the sustainability and success of a company. As a discipline dedicated to managing human resources—recognized as the most valuable asset—HRM aims to achieve organizational goals and optimize performance. The irreplaceable role of humans in production, innovation, and achieving organizational objectives underscores the critical importance of HRM. Even with advanced technology and superior resources, organizational goals are difficult to achieve without active human involvement. HRM encompasses key aspects, including recruitment, selection, development, and performance management. Human resources contribute significantly through their talents, motivation, creativity, and innovation, all of which support organizational sustainability. The primary focus of HRM is to ensure the optimal and efficient utilization of human resources by creating a conducive work environment, providing continuous training and development opportunities, and maintaining harmonious work relationships. The strategic importance of HRM is further demonstrated by its capacity to address complex organizational challenges, such as formulating effective recruitment strategies, implementing training programs, and improving workforce quality. The HR department plays a critical role in designing policies and strategies to ensure a competent workforce that aligns with organizational needs. Consequently, HRM serves as an integral component of the overall management system within an organization. This study employs a literature review methodology, drawing on a wide range of sources, including books, national and international journal articles, and other supporting references. The objective is to provide a comprehensive understanding of the critical role HRM plays in supporting companies to achieve their objectives. HRM not only functions as an administrative manager but also as a key driver, prepared, willing, and capable of making significant contributions to organizational success.